Microwave effects on the electrochemical deposition of copper - Sur, UK; Marken, F; Compton, R; Coles, B (2004)
The effects of microwave radiation on the electro-deposition of copper metal on platinum, gold, and carbon electrode surfaces are studied by cyclic voltammetry and scanning electron microscopy. Electrochemical experiments under microwave conditions are carried out in a conventional three-electrode electrochemical cell placed into a 2.45 GHz microwave cavity. The microwave effect is associated with steady state electrode temperatures of up to 400 K and mass transport enhancements, which are both electrode size and electrode material dependent. The most dramatic mass transport effects are observed at 25 μm diameter platinum microelectrodes with limiting current increases of more than two orders of magnitude. The morphology of the copper deposit at 50 μm diameter platinum electrodes is shown to change from dendritic to cauliflower-type at high microwave intensities. In situ thermal de-complexation of Cu2+ cations in the presence of a strong complexing agent bovine serum albumin (BSA) is achieved under the microwave conditions.